Neutron-Driven Nucleosynthesis in Stellar Plasma - Spartà, R.; La Cognata, M.; Guardo, G. L.; Palmerini, S.; Sergi, M. L.; D’Agata, G.; Lamia, L.; Lattuada, D.; Oliva, A. A.; Pizzone, R. G.; Rapisarda, G. G.; Romano, S.; et al. (Frontiers in Physics, 2022)
A large uncertainty for the slow neutron capture nucleosynthesis (s-process) models is caused by the amount of neutrons available to the process itself. This quantity is strongly affected by the $^{13}$C($α$,n)$^{16}$O and $^{22}$Ne($α$,n)$^{25}$Mg reaction cross sections, whose measurements at energies corresponding to the s-process thermal conditions ($\sim$10$^2$ keV) are mainly hampered by the Coulomb barrier. For this reason, indirect approaches could offer a complementary way of investigation and, among these, the Trojan Horse Method (THM) has been applied to determine these cross sections overcoming the Coulomb barrier. With this approach, a low-energy binary reaction cross section can be obtained selecting the quasi-free contribution from a suitable three-body reaction cross section, taking advantage of the cluster structure of proper nuclei.